2022
DOI: 10.3390/gels8080493
|View full text |Cite
|
Sign up to set email alerts
|

Linking Processing Parameters and Rheology to Optimize Additive Manufacturing of k-Carrageenan Gel Systems

Abstract: Additive manufacturing—in particular, three-dimensional (3D) printing—has been introduced since the late 1980s, offering a novel paradigm for engineering design and manufacturing, as it allows the fabrication of very complex structures. Additive manufacturing of hydrogels is a very popular method to produce scaffolds to be used in tissue engineering and other biomedical applications, as well as in other advanced technological areas. When printing a thermoreversible physical hydrogel, a subtle balance between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Furthermore, all scaffolds that were printed at 37 °C had a perfect reproducibility, independently of the nozzle size used, and all scaffolds printed at this temperature that were wet were significantly different from those that were dry, with their mean Pr values being nearly the optimum value of 1 ( p < 0.001, Figure b) . Hence, it was concluded that a temperature of 37 °C is the best temperature for printing scaffolds as it promotes good gelation conditions in order for a continuous, smooth, and uniform filament extrusion to manufacture grid constructs with well-formed squared pores . This was also applicable for scaffolds with other infill densities, namely, 60, 80, and 100%, using the G25 extrusion nozzle (Figure ).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Furthermore, all scaffolds that were printed at 37 °C had a perfect reproducibility, independently of the nozzle size used, and all scaffolds printed at this temperature that were wet were significantly different from those that were dry, with their mean Pr values being nearly the optimum value of 1 ( p < 0.001, Figure b) . Hence, it was concluded that a temperature of 37 °C is the best temperature for printing scaffolds as it promotes good gelation conditions in order for a continuous, smooth, and uniform filament extrusion to manufacture grid constructs with well-formed squared pores . This was also applicable for scaffolds with other infill densities, namely, 60, 80, and 100%, using the G25 extrusion nozzle (Figure ).…”
Section: Resultsmentioning
confidence: 91%
“…51 Hence, it was concluded that a temperature of 37 °C is the best temperature for printing scaffolds as it promotes good gelation conditions in order for a continuous, smooth, and uniform filament extrusion to manufacture grid constructs with well-formed squared pores. 53 This was also applicable for scaffolds with other infill densities, namely, 60, 80, and 100%, using the G25 extrusion nozzle (Figure 6). CS has been reported to contribute to the formation of compact hydrogels used for 3D printing, though by itself, CS is not sufficient to print scaffolds that have stable structures.…”
Section: Dl(%)mentioning
confidence: 82%
See 1 more Smart Citation
“…There is a minimum adhesion strength at the print speed of 80 mm/s for the virgin PLA. Russo Spena et al 44 investigated the characteristic time, defined as the duration required for the deposition of two consecutive filament layers, as a function of print speed. Their findings indicate that longer depositing times or slower printing speeds result in enhanced adhesion to the previous layer, thus contributing to improved quality of the printed parts.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Deformation forces or temperature can provide sufficient energy to break these bonds, eventually reaching a flowing state lacking any interconnected microstructure. 70 Humins, as a physical gel, are prone to undergo this transition, not exclusively under flow (developing a yield stress) but also when exposed to elevated temperatures. For this purpose, humins that were previously reacted at 80 °C for 300 min were then submitted to a temperature ramp of 2 °C min −1 and the corresponding viscoelastic response was measured.…”
Section: Resultsmentioning
confidence: 99%